Research on Cutting Characteristics of Rock Plate with Two Sides Fixed and Two Sides Free - Zhenguo Lu; Qingliang Zeng; Zhihai Liu; Guanshun Gao; Peisi Zhong (Advances in Materials Science and Engineering)
Conical pick wear is an urgent problem in the roadway excavation caused by hard rock difficult to break. The traditional method of increasing cutting power to improve cutting performance of conical pick significantly increases pick wear. In the paper, a saw blade and conical pick combined cutting method is proposed based on increased free surface. To research the fracture morphology and cutting force of rock plate, theoretical, numerical, and experimental methods are used. By theoretical research, the bending mechanical model of rock plate bending is established. The cutting position and the junction between the free sides and fixed sides are preferentially broken. A numerical model combining the erosion and damage constitutive model is built, and the cutting process of rock plate was presented. According to rock plate experiment, the peak cutting force increases with the increasing uniaxial compressive strength, thickness of rock plate, and cutting depth of conical pick and decreases with the increasing width and height of rock plate. Exponential relationships exist between peak cutting force and thickness, width and height of rock plate, and cutting depth of conical pick. Linear relationship exists between peak cutting force and uniaxial compressive strength. The size of rock fragments increases with uniaxial compressive strength, width, and height of rock plate.